2002
DOI: 10.1038/sj.jhh.1001448
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to non-compliance with antihypertensive drug therapy

Abstract: The objectives were to study the associations of perceived health care-related and patient-related factors with self-reported noncompliance with antihypertensive treatment. General practitioners identified all of their hypertensive patients in 26 health centres during 1 week in 1996 (n = 2219). A total of 1782 (80%) patients participated in the study, of whom 1561 were on antihypertensive medication. Based on 82 opinion statements in two questionnaires, 14 problem indices were formed by using factor analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
2
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 20 publications
4
44
2
12
Order By: Relevance
“…Although, this problem cannot be completely solved, there will be a cost-effective solution provided by clinical pharmacist to those patients according to their existing conditions. Some reports also indicated that pharmacist interventions were not likely to gain a statistically significant improvement in this outcome when medication adherence at baseline is already high (about 75%) (Chabot et al, 2003;Jokisalo et al, 2003), and in our study, low baseline medication adherence (47.5%) made it feasible for pharmaceutical intervention to get an obvious positive effect in this outcome and hence in treatment outcomes. And in the end, our percentage of low medication adherence accounted for 24.8%, which perfectly matched that in other studies.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Although, this problem cannot be completely solved, there will be a cost-effective solution provided by clinical pharmacist to those patients according to their existing conditions. Some reports also indicated that pharmacist interventions were not likely to gain a statistically significant improvement in this outcome when medication adherence at baseline is already high (about 75%) (Chabot et al, 2003;Jokisalo et al, 2003), and in our study, low baseline medication adherence (47.5%) made it feasible for pharmaceutical intervention to get an obvious positive effect in this outcome and hence in treatment outcomes. And in the end, our percentage of low medication adherence accounted for 24.8%, which perfectly matched that in other studies.…”
Section: Discussionsupporting
confidence: 42%
“…The medication compliance of patients was poor previously due to some reasons, such as the complicated and hard-to-control disease course, the life-time dosing period, the economic condition of the patients as well as the irrational and complex drug use; thereby, most of the patients cannot be healed thoroughly (Jokisalo et al, 2003). This research on medication compliance of hypertensive patients was mainly conducted by pharmacist in the perspective of clinical medicine and clinical nursing.…”
Section: Discussionmentioning
confidence: 99%
“…33 Many studies did not report duration of hypertension to have a significant association with treatment compliance similar to our study. 12,34,35 There was no significant difference among patients with differing durations of disease, but compliance score was higher in those patients who had taken antihypertensive drugs for longer than 5 years in a cross-sectional study in Iran. 36 Compliance with a treatment regimen was positively correlated with duration of hypertension in study in Kingdom of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 93%
“…[11][12][13][14][15][16] Determinants of poor BP control are multi-level. That is, previously identified factors that contribute to poor BP control have included physician-related factors, such as physician age, 17 willingness to accept high BP values 18 and so-called 'therapeutic inertia, ' 19 as well as patient-related factors, including age, 20,21 treatment adherence 22,23 and gender. [24][25][26] An area of clinical interest that has not received attention is whether or not the multi-level determinants of BP control are gender-specific.…”
Section: Introductionmentioning
confidence: 99%